Functional role for suppression of the insular–striatal circuit in modulating interoceptive effects of alcohol. (27th September 2017) - Jaramillo, Anel A.; Agan, Verda E.; Makhijani, Viren H.; Pedroza, Stephen; McElligott, Zoe A.; Besheer, Joyce
Abstract: The insular cortex (IC) is a region proposed to modulate, in part, interoceptive states and motivated behavior. Interestingly, IC dysfunction and deficits in interoceptive processing are often found among individuals with substance‐use disorders. Furthermore, the IC projects to the nucleus accumbens core (AcbC), a region known to modulate the discriminative stimulus/interoceptive effects of alcohol and other drug‐related behaviors. Therefore, the goal of the present work was to investigate the possible role of the IC ➔ AcbC circuit in modulating the interoceptive effects of alcohol. Thus, we utilized a chemogenetic technique (hM4Di designer receptor activation by designer drugs) to silence neuronal activity in the IC of rats trained to discriminate alcohol (1 g/kg, IG) versus water using an operant or Pavlovian alcohol discrimination procedure. Chemogenetic silencing of the IC or IC ➔ AcbC neuronal projections resulted in potentiated sensitivity to the interoceptive effects of alcohol in both the operant and Pavlovian tasks. Together, these data provide critical evidence for the nature of the complex IC circuitry and, specifically, suppression of the insular–striatal circuit in modulating behavior under a drug stimulus control. Abstract : We examined the insular cortex (IC) and its projections to the nucleus accumbens core (AcbC) in modulating the interoceptive effects of alcohol in two alcohol discrimination tasks (operant and Pavlovian) in rats. Silencing IC ➔ AcbC projections (using chemogenetics) potentiated the effects of alcohol and produced 'alcohol‐like' effects. This increased sensitivity to alcohol was more pronounced than silencing the IC alone. These findings show the critical nature of IC circuitry in an alcohol drug state, which can have implications for drinking/seeking behaviors. CNO, clozapine‐ n ‐oxide